Pengaruh E-Service Quality, Word Of Mouth (Wom), Dan Promosi Produk Terhadap Kepuasan Pelanggan Pengguna Aplikasi Pelni Mobile di Pt Pelni Cabang Tanjungpinang - Okta Rolland Erwindika; Paramita, Bunga; Fani, Lastri Anggi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of e-service quality, word of mouth (WOM), and product promotion on customer satisfaction among users of the PELNI Mobile application at PT PELNI Tanjungpinang Branch. This study employed a quantitative approach using a survey method involving 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS version 27. The results indicate that, both simultaneously and partially, e-service quality, WOM, and product promotion have a significant effect on customer satisfaction. These findings suggest that improving digital service quality, encouraging positive communication among users, and implementing effective promotional strategies can enhance the satisfaction of PELNI Mobile application users.